Familial primary osteoarthropathy: A case report with unusual dental findings - Vela D Desai; Sunil MV Kumar; Sahil Maghu (Wolters Kluwer Medknow Publications, 2015)
Pachydermoperiostosis (PDP) is a rare osteo-arthro-dermopathic syndrome, the diagnosis of which can be made on the basis of the classic clinical and radiological presentations. The primary form of the disease, also called as Touraine-Solente-Gole Syndrome, contributes to approximately 3-5% of the cases of hypertrophic osteoarthropathy (HOA). The authors present here a rare case of familial primary osteoarthropathy with significant dental findings which, to the best of our knowledge, is seldom reported in English literature.